Influence of Arachidonic Acid on Catecholamine Secretion in the Perfused Rat Adrenal Medulla - Lim, Dong-Yoon (Korean J Intern Med, 1993)
The present study was conducted to investigate the influence of arachidonic acid, which is known to be an important unsaturated fatty acid component of membrane phospholipids and to be liberated by phospholipase A(2) action, on secretion of catecholamines (CA) from the isolated perfused rat adrenal glands and to clarify the mechanism of its action. Arachidonic acid (10 uM) perfused into an adrenal gland of the rat for 20 min caused a significant inhibition of CA secretion evoked by ACh (5.32×10(−3) M), DMPP (10(−4) M) and muscarine (10(−4) M) while it did not affect that induced by excess K(+) (5.6×10(−2) M). Arachidonic acid, in the presence of ouabain (100 uM), an inhibitor of Na(+), K(+) -ATPase, also produced a marked inhibitory effect of CA secretion evoked by ACh, DMPP and muscarine but did not modify the secretory effect of excess K(+). The perfusion of arachidonic acid along with indomethacin (30 uM), which is an inhibitor of cyclooxygenase, for 20 min attenuated markedly CA secretory effect evoked by ACh, DMPP and muscarine while it did not influence that by excess K(+). Prostaglandin F(2) alpha perfused in a retrograde direction for 20 min inhibited greatly the CA secretion evoked by DMPP but did not affect the effect evoked by excess K(+). All of arachidonic acid, ouabain, indomethacin and prostaglandin F(2) alpha used in the present study did not affect the spontaneous basal release of CA in the perfused rat adrenal glands. Taken together, these experimental results suggest that arachidonic acid, as well as prostaglandin F(2) alpha, cause the inhibitory action of CA secretion evoked by cholinergic receptor-mediated stimulation, but not by membrane depolarization, and also play a modulatory role in regulating CA secretion from the rat adrenal medulla.